Hydrogen peroxide-mediated oxidative stress induces inflammasome activation in term human placental explants - Nunes, Priscila Rezeck [UNESP]; Peracoli, Maria Terezinha Serrao [UNESP]; Romao-Veiga, Mariana [UNESP]; Matias, Mariana Leticia [UNESP]; Ribeiro, Vanessa Rocha [UNESP]; Fernandes, Célio Junior da Costa [UNESP]; Peracoli, Jose Carlos [UNESP]; Rodrigues, Jose Ricardo [UNESP]; De Oliveira, Leandro [UNESP] (Elsevier, 2018)
Background: The placenta is a multifunctional organ that can suffer with imbalances between pro- and antioxidant molecules, contributing for inflammatory imbalance. The inflammation generated by oxidative stress may induce inflammasome activation, an essential complex for pro-inflammatory cytokine production. Objective: The aim of this study was to evaluate whether hydrogen peroxide (H2O2) mediated oxidative stress induces inflammasome activation on placental explants. Study design: Tissue cultures of placental explants obtained from normotensive pregnant women were performed in different concentrations of H2O2. Gene expressions of NLRP3, caspase-1, IL-1β TNF-α and IL-10 were evaluated by qPCR. Superoxide dismutase (SOD), catalase, Heat shock protein 70 (Hsp70), Caspase-1, TNF-α IL-1β IL-10 and human Chorionic Gonadotropin (hCG) were determined by ELISA. Results: Concentrations of catalase, Hsp70, hCG and SOD were higher in cultures with 100 and 1000 µM H2O2 compared to controls. Gene and protein expressions of TNF-α and IL-1β were elevated in cultures with 1000 μM H2O2 compared to controls. This concentration led to inflammasome activation, by increasing gene expressions of NLRP3, caspase-1 and IL-1β. In contrast, gene and protein expressions of IL-10 were reduced at 100 and 1000 μM H2O2. Protein expression of caspase-1 was higher in cultures of 100 μM H2O2 compared to controls. Treatment with Glybenclamide at 200 μM was used to prevent NLRP3 inflammasome activation. This concentration reduced protein expression of caspase-1 compared to culture with only H2O2 and control cultures. Conclusions: Our results confirm that H2O2 induces oxidative stress on placental explants and demonstrate that cell responses to this stress involve inflammasome activation.
Keywords: Cytokines; Inflammasome; Oxidative stress; Placental explants